Pancreatic cancer challenge in 52 Asian countries: age-centric insights and the role of modifiable risk factors (1990-2019) - Xiang, Xin; Chen, Xuejie; He, Yue; Wang, Yiwei; Xia, Weitong; Ye, Shuyu; Wang, Sidan; Xiao, Yi; Li, Quansi; Wang, Xiaoyan; Luo, Weiwei; Li, Jingbo (Frontiers in Oncology, 2023)
Background: Pancreatic cancer is notoriousrenowned for its high globalelevated incidence and mortality rates on a global scale. The disease burden of pancreatic cancer is anticipated to increase, especiallyparticularly in Asia, due to its vast and rapidly aging population. Pancreatic cancer, notorious for its high global incidence, mortality, requires early detection and intervention strategies. The disease burden is expected to grow, particularly in Asia, due to its vast, rapidly aging population.Methods: Data from the Global Burden of Disease 2019 were analyzed for pancreatic cancer burden across 52 countries in Asia, including the incidence, mortality, and disability-adjusted life years (DALY) for pancreatic cancer, with a focus on risk factors such as high body mass index (BMI), elevated fasting plasma glucose, and smoking. We applied the Estimated Annual Percentage Change, the Age-Period-Cohort model, and decomposition analysis to evaluate incidence trends and effects.Results: From 1990 to 2019, both incidence and mortality rates of pancreatic cancer in Asia significantly increased, with an average annual standardized incidence rate change of 1.73%. Males consistently exhibited higher rates than females, with tobacco usesmoking as a key risk factor. Central Asia reported the highest rates, and South Asia the lowest. The incidenceIncidence rose with age, peaking in those aged 70~74groups. An elevated The disease burden was observed,increased in all age groups, particularly in populations aged 55 and above, representing 84.41% of total cases in 2019, up from 79.01% in 1990. Pancreatic cancer ranked the fifth in incidence among six major gastrointestinal tumors but led topresented a significant growth rate of mortality and DALY.Conclusion: With Asia's the growing, aging population in Asia, the pancreatic cancer burden is projected to escalate, presenting bringing a significant public health challenge. Hence, comprehensive public health strategies emphasizing early detection, risk modification, and optimized treatment of pancreatic cancer are imperative.